Biologi dan Identifikasi Serta Prospek Usaha Trigona, sp di Kebun Raya Universitas Halu Oleo - Awaluddin, Awaluddin; Hisein, Wa Ode Siti Anima; Dedu, La Ode Arfan; Pakki, Terry; Yuswana, Agung (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2018)
Development and reproduction colonies of Trigona sp., continues to experience a downturn, it is causing livestock business is not growing.  Therefore, understanding the method of reproduction biology of knowledge based on colony Trigona sp. should be developed in order to make available the bank colony Trigona, sp.  The research was funded in the area of the Botanical Garden of the Halu Oleo University beginning with: (1) identification of species, Trigona sp., (2) Identification of the egg stage, Larva Pupah Trigona, sp.  The research results showed that the species found in the Botanical Garden and the surrounding the Halu Oleo University is Tetragonula biroi.  With the average of the old stadium eggs average 3.67 days, stadium larvae of 6.67 yesterday and stadium Pupah 12.56 today. This research is expected to be a medium of instruction, students, farmer community groups